Influence of superdispersed additives to crude materials on morphology of coke - A. V. Petrov; N. J. Beilina (Тонкие химические технологии, 2010)
Influence of additives to the crude product of coking on the properties of coke was studied. It was shown that an introduction of coke additives into the crude product of coking considerably affects the morphology of the resulting coke. (The average point of coke microstructure decreases by 22 - 30%).